Connatural management approach to preparation and development of individuals in the business environment - Kolenak, Jiri; Ambrozová, Eva; Pokorný, Vratislav (Business: Theory and Practice, 2016)
Article develops modern trends in management, using knowledge of cognitive and behavioural sciences. It presents the concept of subtle skills and a connatural management approach. It presents the results of research on the relationship between stress, mental condition and the level of critical thinking, problem solving and decision making. To achieve these goals we have used results of a psycho-diagnostic research which all participants of managerial training X-tream Management were subjected to.